Pelaksanaan Pemeriksaan Tes Psikologi Calon Karyawan Guru Yayasan Sosial Pendidikan PT Pupuk Sriwidjaja Palembang - Desy Arisandy; Kania Putri Maharani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
Recruitment and selection are essential processes for acquiring competent human resources who meet organizational needs. In addition to evaluating applicants' knowledge and skills, the selection process should also assess psychological aspects, including intellectual ability, personality, motivation, and work attitude. This community service activity aimed to support the implementation of psychological testing for prospective teacher employees of the Pupuk Sriwidjaja Educational and Social Foundation, Palembang. The method employed involved assisting in the administration of psychological assessments through participant registration, test preparation, test administration and supervision, test scoring, and data entry. The psychological instruments used included the Culture Fair Intelligence Test (CFIT), DISC, Kraepelin, and PAPI Kostick. The results demonstrated that all stages of the psychological testing process were carried out systematically and in accordance with established procedures. The use of these psychological assessment instruments provided objective information regarding participants' intellectual abilities, personality characteristics, concentration, work endurance, and behavioral preferences. These findings served as an important basis for supporting the recruitment and selection process, enabling the organization to identify prospective employees whose competencies and characteristics align with organizational needs and job requirements. This activity is expected to contribute to improving the quality of recruitment and selection through standardized and objective psychological assessment procedures.